Photocatalytic debromination of polybrominated diphenyl ethers (PBDEs) on metal doped TiO2 nanocomposites: Mechanisms and pathways. (June 2019) - Wang, Rui; Tang, Ting; Wei, Yanchun; Dang, Dai; Huang, Kaibo; Chen, Xingwei; Yin, Hua; Tao, Xueqin; Lin, Zhang; Dang, Zhi; Lu, Guining
Abstract: Nanoparticles of four noble metal doped titanium dioxide (i.e., Pd/TiO2, Ag/TiO2, Pt/TiO2 and Cu/TiO2 ) were synthesized and investigated for their effectiveness to degrade polybrominated diphenyl ethers (PBDEs) under UV light. All the investigated noble metal additives can greatly enhance the performance of TiO2 to degrade 2, 2′, 4′, 4′-tetrabromodiphenyl ether (BDE-47). However, the debromination pathways of BDE-47 in Ag/TiO2 and Cu/TiO2 systems are just contrary to those in Pd/TiO2 and Pt/TiO2 systems, and there was an induction period in the former systems but not in the latter systems. The hydrogenation experiment suggests a direct H-atom transfer mechanism in Pd/TiO2 and Pt/TiO2 systems, while in Ag/TiO2 and Cu/TiO2 systems, electron transfer is still the dominant mechanism. Electronic method was applied to explain why BDE-47 exhibit different debromination pathways based on different degradation mechanism. In addition, oxygen was proved to be able to capture both electrons and H atoms, and thus can greatly inhibit the degradation of PBDEs in all investigated systems. Finally, the merit and demerit of each metal doped TiO2 were discussed in detail, including the reactivity, stability and the generation of byproducts. We proposed our study greatly enhance our understanding on the mechanisms of PBDE degradation in various metal doped TiO2 systems. Graphical abstract: Unlabelled Image Highlights: Metal catalysts promote the reactivities of TiO2 via different mechanisms. BDE-47 exhibits different pathways in e-transfer and H-transfer processes. O2 can capture both electrons and H atom species.